Literature Study: The Effect of Giving Chitosan Water Gel (Hydrogel) on Healing Diabetic Ulcers Based on In Vivo Studies with Animal Models - Zahratul Noreisza Rakhmadi; Erina Yatmasari; Prawesty Diah Utami (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Diabetic ulcers are one of the most common chronic complications and cause infection, gangrene to leg amputation if the treatment given is not appropriate. Chitosan has anti-microbial properties that make the wound area smaller and are anti-inflammatory to reduce pain. Water gel (hydrogel), which is water, is easily absorbed by the skin and penetrates perfectly into the wound so that it provides a moist effect and prevents bacteria from entering. This study aims to determine the effect of giving chitosan water gel (hydrogel) on the healing of diabetic ulcers. This study uses a literature study method by searching for related journals using keywords, then selected based on the last 5 years and indexed in SINTA, Google Scholar or Scopus, and the final results are 13 journals. This study took place in May - November 2021. The results of this study reported that the administration of chitosan water gel (hydrogel) combined with other ingredients for healing diabetic ulcers gave the same results. The results obtained are reducing inflammation, re-epithelializing wounds, accelerating angiogenesis, accelerating the formation of collagen and granulation tissue, and accelerating wound healing. Although all studies have the same results, the healing time produced by each study is different, this is because each ingredient used has a different content. The average wound changes were seen on the 3rd, 5th, 7th day and the wound healed completely on the 14th day. This study concludes that the administration of chitosan water gel (hydrogel) affects the healing of diabetic ulcer wounds in combination with other ingredients. because the time needed to close the wound is faster.